Teaching Legal Ideals through Jurisprudence - TAN, Seow Hon (Institutional Knowledge at Singapore Management University, 2009)
This article examines the value of jurisprudence in legal education. It argues that jurisprudence should be mandated at an early stage of the students' law curriculum as the legal ideals that may be imparted through a jurisprudence course cannot be adequately taught in a professional ethics course or through teaching jurisprudential perspectives in doctrinal subjects. Law schools have a special responsibility to get students thinking about what law is, what makes law legitimate, and how law is related to justice, morality, politics and rationality. A mandatory jurisprudence course should be intentionally structured along these themes.